Taá¹awwur al-TarbÄ«yah al-IslÄmÄ«yah (Surau) fÄ« Minangkabau - Mulyani, Mulyani (Studia Islamika, 1997)
The development of Islam in Minangkabau is inseparable from the development of Islamic education and broadcasting that took place in the surau-surau. Position surau in Minangkabau as important as the position in the context of the development of Islamic boarding schools in Java. As pesantren, surau a printer agent of the scholars responsible for transmitting the teachings of Islam and building societies to be the people who obey the above teachings.DOI:Â 10.15408/sdi.v4i1.790